Hubungan antara Adiksi Internet, Kualitas Tidur dan Tingkat Kecemasan Terhadap Kecerdasan Sosial pada Remaja Usia SMA - Christopher Lawrence; Roni Linson Girsang; Iswadi; Imti Tsalil Amri (Universitas Adiwangsa Jambi, 2023)
This study aims to analyze the relationship between internet addiction, sleep quality, and anxiety levels on social intelligence among high school adolescents in Jambi in 2023. Adolescence is a critical period in social and emotional development, highly influenced by digital lifestyle and mental health factors. This research employed a quantitative approach using a survey method administered to a selected group of high school students through purposive sampling. The research instruments included validated standardized questionnaires to measure internet addiction, sleep quality, anxiety, and social intelligence. Data were analyzed using multiple linear regression to examine the simultaneous and partial effects of the three independent variables on social intelligence. The results revealed a significant relationship between internet addiction, sleep quality, and anxiety levels with adolescents’ social intelligence. Specifically, internet addiction and anxiety showed negative effects, while sleep quality demonstrated a positive effect on social intelligence. These findings hold important implications for developing interventions that support adolescent mental and social well-being in the digital age.